2012
DOI: 10.7227/ijs.20.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Connectedness in the Lives of Older People in Ireland: A Study of the Communal Participation of Older People in Two Geographic Localities

Abstract: This paper presents an analysis of the connectedness of older people in two sample areas, one urban and one rural, in Ireland. The paper is based on a study ofthe communal participation of older people in two geographic localities; Rathmore, a suburban area of Dublin, and Rathbeg, a rural area in County Donegal, conducted between 2000 and 2005. A multi-stage study that used both qualitative and quantitative methods examined significant communal interactions of older people across a range of arenas, including l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(51 citation statements)
references
References 12 publications
(8 reference statements)
4
46
0
1
Order By: Relevance
“…One study of life satisfaction in older people with reduced ADL capacity across six European countries suggests that personal rather than environmental factors are important for life satisfaction (Borg et al 2008). This is supported by other research which suggests that positive social relations are a significant source of satisfaction for older people (Gallagher 2012).…”
Section: Individual Well-being: Quality Of Life Life Satisfaction Lmentioning
confidence: 90%
“…One study of life satisfaction in older people with reduced ADL capacity across six European countries suggests that personal rather than environmental factors are important for life satisfaction (Borg et al 2008). This is supported by other research which suggests that positive social relations are a significant source of satisfaction for older people (Gallagher 2012).…”
Section: Individual Well-being: Quality Of Life Life Satisfaction Lmentioning
confidence: 90%
“…Research exploring older adults’ (60 + years) views on the process of healthy ageing emphasises the importance of social engagement and participation, facilitated through “social involvement, stimulation and/or participation in various activities” (Cosco, Prina, Perales, Stephan, & Brayne, ; Reichstadt, Sengupta, Depp, Palinkas, & Jeste, ), even among those with illness or disability (Cosco et al, ). An active lifestyle with high social involvement positively influences older adults’ physiological health (Shankar, McMunn, Banks, & Steptoe, ), mental health (Forsman, Schierenbeck, & Wahlbeck, ), cognitive function (Engelhardt, Buber, Skirbekk, & Prskawetz, ; Glei et al, ), self‐esteem and a sense of meaning (Gallagher, ; Santini, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…At times, participants even brought their own food to the restaurant! Similar research in Ireland found that older people use meals at day centres and coffees at the local pub during the day as a means of staying connected with others in an informal way (Gallagher, 2008(Gallagher, , 2012Haslett, 2005;Walsh and Harvey, 2011). In fact, for some, it was the only time that they had companionship during meal time (Haslett, 2005).…”
Section: Implications Of Trends For the Elderly In Terms Of Health Anmentioning
confidence: 87%
“…Some elderly use drinking and dining out as a means of combating loneliness and isolation (Cheang, 2002;Gallagher, 2012;Sydner et al, 2007). Other research into ageing also reaffirms the importance of commensality (Fjellström, 2009).…”
Section: Implications Of Trends For the Elderly In Terms Of Health Anmentioning
confidence: 99%